Human neural stem cells drug product: Microsatellite instability analysis. - Valentina Grespi; Cecilia Caprera; Claudia Ricciolini; Ilaria Bicchi; Gianmarco Muzi; Matteo Corsi; Stefano Ascani; Angelo Luigi Vescovi; Maurizio Gelati (PLoS ONE, 2022)
Introduction In central nervous system neurodegenerative disorders, stem cell-based therapies should be considered as a promising therapeutic approach. The safe use of human Neural Stem Cells (hNSCs) for the treatment of several neurological diseases is currently under evaluation of phase I/II clinical trials. Clinical application of hNSCs require the development of GMP standardized protocols capable of generating high quantities of reproducible and well characterized stem cells bearing stable functional and genetic properties. Aim The aim of this study was to evaluate possible instabilities or modifications of the microsatellite loci in different culture passages because high culture passages represent an in vitro replicative stress leading to senescence. Experimental method: The hNSCs were characterized at different culture time points, from passage 2 to passage 25, by genetic typing at ten microsatellite loci. Conclusion We showed that genetic stability at microsatellite loci is maintained by the cells even at high passages adding a further demonstration of the safety of our hNSCs GMP culture method.